5G network co-construction and sharing mode - Yuhua HU; Yingqi TANG; Bei LI (Dianxin kexue)
With the large-scale commercial deployment of 5G,the problems of high unit price of 5G network equipment,large construction investment,high power consumption of equipment and high operation cost are increasingly prominent.In addition to high-quality construction,improving the operation efficiency and efficiency of 5G network,and building and sharing become a new mode of network construction and operation explored by operators.5G network co-construction and sharing from the aspects of network architecture and frequency use were analyzed,and three kinds of network co-construction and sharing technology schemes were put forward:independent carrier,shared carrier and different network roaming.The advantages and disadvantages of each scheme were compared,and the applicable scenarios were analyzed,the current challenges were pointed out.It was summarized how to choose a reasonable deployment mode to promote co construction and sharing.